2005
DOI: 10.1111/j.1526-100x.2005.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Doubling Limestone Sand Applications in Two Acidic Southwestern Pennsylvania Streams

Abstract: We studied the effects of limestone sand additions in Bear and Rock runs, two chronically and episodically acidified streams in southwestern Pennsylvania, U.S.A. Linn Run, a nearby episodically acidified stream, served as a reference stream. Our objectives were to evaluate the effects of doubling recommended limestone sand amounts on water quality and macroinvertebrates on Bear and Rock runs and to assess substrate changes resulting from limestone sand inundation. Approximately 23 and 6 tonnes of limestone san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…Specifically, we found that benthic-macroinvertebrate density, and the percentage of acid-sensitive taxa biomass were strongly dependent on spatial proximity to limestone treatment. Our findings are consistent with those of several studies that have observed incomplete recovery of benthic-macroinvertebrate communities in limestone-treated streams , Bradley and Ormerod 2002, Keener and Sharpe 2005.…”
Section: Mixing-zone Complicationssupporting
confidence: 93%
See 4 more Smart Citations
“…Specifically, we found that benthic-macroinvertebrate density, and the percentage of acid-sensitive taxa biomass were strongly dependent on spatial proximity to limestone treatment. Our findings are consistent with those of several studies that have observed incomplete recovery of benthic-macroinvertebrate communities in limestone-treated streams , Bradley and Ormerod 2002, Keener and Sharpe 2005.…”
Section: Mixing-zone Complicationssupporting
confidence: 93%
“…In our study, aluminum concentrations in treated steams were either intermediate to circumneutral and acidic-stream concentrations or more similar to acidic conditions. These findings are very similar to those of Keener and Sharpe (2005). In contrast, most historical limestone-remediation studies have shown that limestone treatment significantly reduces aluminum concentrations compared to acidic control reaches (Downey et al 1994, Simmons and Doyle 1996, Hudy et al 2000, LeFevre and Sharpe 2002 and even to concentrations similar to those found in circumneutral streams (Rundle et al 1995).…”
Section: Acidic Watershedsupporting
confidence: 73%
See 3 more Smart Citations